AeroSense Monitor Integrasi Sensor DHT11 dan MQ135 untuk Pemantauan Kualitas Udara Berbasis Arduino Uno - Muhammad Erik; Furkhon Nurdiyanto; Rahmat Hidayat (Jurnal Komputer dan Elektro Sains, 2024)
Clean air is a basic necessity, but air pollution in Indonesia's major cities has increased significantly. The lack of air quality monitoring facilities in certain areas leads to a lack of public awareness of air pollution levels, which can adversely affect health. As a solution, the development of AeroSenseMonitor, an Arduino Uno-based air quality monitoring tool with DHT11 and MQ135 sensors, is proposed. This tool is expected to provide accurate information on air quality, enabling people to take preventive measures and protect their health. By raising awareness of the importance of clean air, it is hoped that the AeroSenseMonitor can be the first step in addressing the negative impacts of air pollution in Indonesia.